Pulmonary artery growth during treatment with oral prostaglandin E2 in ductus dependent cyanotic congenital heart disease. Issue 3 (March 1983) - MacMahon, P; Gorham, P F; Arnold, R; Wilkinson, J L; Hamilton, D I
Abstract : Growth of the pulmonary arteries was assessed in 11 patients with cyanotic congenital heart disease treated with oral prostaglandin E2. Each patient was dependent on patency of the ductus arteriosus for maintenance of the pulmonary circulation. Measurements were made initially from angiographic data obtained in the neonatal period. Subsequent assessments were made at the time of surgery after an interval of 2-8 months, during which time all the infants had gained weight normally. Comparisons were made with data obtained from 13 normal necropsy specimens. In only 4 of the 11 patients had the pulmonary arteries grown appreciably during the treatment period. In 2 patients no growth occurred, while in 5 patients the pulmonary arteries had actually become smaller. It had been hoped that the pulmonary arteries would grow in all 11 patients during this period, facilitating later surgical intervention. In patients with ductus-dependent cyanotic congenital heart disease, the prolonged use of oral prostaglandin E2 should be restricted to patients in whom the pulmonary arteries are too small to allow a palliative operation to be performed initially.